Pengaruh Partisipasi Anggaran, Sistem Pelaporan Terhadap Implementasi Akuntansi Pertanggungjawaban Dengan Komitmen Organisasi Sebagai Variabel Moderating PT. Perkebunan Nusantara IV Medan - Nasution, Affrina; Januri, Januri; Sari, Maya (CV. ITTC INDONESIA, 2024)
This study aims to analyze the influence of human resource (HR) competence and the Regional Government Information System (SIPD) on the implementation of performance-based budgeting at the UPT Puskesmas of the Medan City Health Office. In addition, this study also looks at how organizational commitment moderates the influence of HR competence and SIPD on the implementation of the budget. The method used is a quantitative associative approach with a Likert Scale-based questionnaire instrument. The research sample consisted of 123 respondents including the Head of the Puskesmas, Technical Activity Implementation Officers (PPTK), and Head of Administration (KTU) from 41 UPT Puskesmas in Medan City. The analysis was carried out using the Structural Equation Modeling (SEM) method with the help of SmartPLS.3 software. The results of the study indicate that HR competence and SIPD effectiveness have a significant effect on the implementation of performance-based budgeting. Organizational commitment has also been shown to moderate this influence, strengthening the relationship between HR competence, SIPD effectiveness, and budget implementation. This finding is important for improving budget management in the health sector.